IMPLEMENTASI PROGRAM MAB UNESCO DI CAGAR BIOSFER GIAM SIAK KECIL-BUKIT BATU, RIAU DALAM MENDUKUNG SDGS KE-15 - Risma, Delra Maulida; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Every country has an interest in pursuing development to enhance the welfare of its people. However, development that neglects environmental considerations can result in severe ecological damage. This study examines how UNESCO's Man and the Biosphere (MAB) program in the Giam Siak Kecil – Bukit Batu Biosphere Reserve, located in Riau Province, supports the achievement of the Sustainable Development Goals (SDGs), particularly Goal 15, which focuses on the protection of terrestrial ecosystems. A qualitative case study approach was used to explore the effectiveness of the MAB program in promoting environmental sustainability amid pressures from extractive industries such as palm oil plantations, mining, and the timber sector. The findings indicate that while the biosphere reserve has made significant contributions to biodiversity conservation and environmental education, it still faces major challenges. These include weak law enforcement, limited community participation, and the dominance of industrial interests that often exploit conservation zones for unsustainable practices. The MAB program is also vulnerable to misuse as a form of greenwashing by industries that seek legitimacy without true commitment to sustainability principles. Therefore, the successful implementation of the MAB program in Indonesia depends heavily on stricter oversight, comprehensive evaluation of the environmental impacts of economic activities, and active involvement of local communities as key ecosystem stewards. The government is also expected to take a firm stance against conservation violations to ensure that development genuinely aligns with sustainable principles. Keywords: Biosphere Reserve, Giam Siak Kecil-Bukit Batu Biosphere Rese, SDGs, Man and Biosphere, UNESCO.